Part One: An Introduction to the Research Process. Issue 4 (April 2015) - Quick, J; Hall, S
Research modules have become a common inclusion to graduate healthcare programmes. To the novice researcher, undertaking a study or dissertation can appear daunting. This article is the first of a series of four that aims to help perioperative practitioners feel more positive about undertaking a project by examining the research process and the theoretical frameworks of qualitative and quantitative approaches. The final of the four articles provides advice on writing a dissertation.